Impaired regenerative capacity and senescence‐associated secretory phenotype in mesenchymal stromal cells from samples of patients with aseptic joint arthroplasty loosening. Issue 2 (2nd April 2021) - Ebert, Regina; Weissenberger, Manuel; Braun, Clemens; Wagenbrenner, Mike; Herrmann, Marietta; Müller‐Deubert, Sigrid; Krug, Melanie; Jakob, Franz; Rudert, Maximilian
Abstract: Aseptic loosening of total hip and knee joint replacements is the most common indication for revision surgery after primary hip and knee arthroplasty. Research suggests that exposure and uptake of wear by mesenchymal stromal cells (MSC) and macrophages results in the secretion of proinflammatory cytokines and local osteolysis, but also impaired cell viability and regenerative capacity of MSC. Therefore, this in vitro study compared the regenerative and differentiation capacity of MSC derived from patients undergoing primary total hip arthroplasty (MSCprim) to MSC derived from patients undergoing revision surgery after aseptic loosening of total hip and knee joint implants (MSCrev). Regenerative capacity was examined by measuring the cumulative population doubling (CPD) in addition to the number of passages until cells stopped proliferating. Osteogenesis and adipogenesis in monolayer cultures were assessed using histological stainings. Furthermore, RT‐PCR was performed to evaluate the relative expression of osteogenic and adipogenic marker genes as well as the expression of markers for a senescence‐associated secretory phenotype (SASP). MSCrev possessed a limited regenerative capacity in comparison to MSCprim. Interestingly, MSCrev also showed an impaired osteogenic and adipogenic differentiation capacity compared to MSCprim and displayed a SASP early after isolation. Whether this is the cause or the consequence of the aseptic loosening of total joint implants remains unclear. Future research should focus on the identification of specific cell markers on MSCprim, which may influence complication rates such as aseptic loosening of total joint arthroplasty to further individualize and optimize total joint arthroplasty.